Penentuan Premi Tahunan Dan Cadangan Premi Dengan Metode New Jersey Asuransi Endowment Status Joint Life Menggunakan Suku Bunga Stokastik - Miasary, Seftina Diyah; Umami, Riza Lathifatul; Siswanah, Emy (UJMC (Unisda Journal of Mathematics and Computer Science), 2023)
Joint life endowment status insurance is insurance that pays out if the participant dies during the policy participant's first death or survives until the conclusion of the insurance period. The purpose of this study is to calculate the amount of joint life endowment status life insurance premium reserves using the New Jersey technique in the CIR model with stochastic interest rates. The CIR model's stochastic interest rate value based on Bank Indonesia interest rates from 2018 to 2022 is 0,075. According to the calculations, the resulting annual premium is lower since the number of individuals who survive is greater than the number of persons who die over the insurance period. Furthermore, the size of the New Jersey premium reserve is zero in the first year and becomes closer to the compensation value as the insurance period proceeds.